2014 16th International Telecommunications Network Strategy and Planning Symposium (Networks) 2014
DOI: 10.1109/netwks.2014.6959207
|View full text |Cite
|
Sign up to set email alerts
|

Free space optics in different (civil and military) application scenarios in combination with other wireless technologies

Abstract: In this paper Free Space Optics (FSO) in combination with other wireless technologies (including WLAN and satellite communications in civil-military-cooperation (CIMIC)) is presented. At first modular communication systems are shown, which allows worldwide access to the Internet or other networks by combining satellite communications, FSO, Wireless LAN, Local Multipoint Distribution System (LMDS) and DVB-T (terrestrial digital video broadcast). Wireless LAN offers connectivity to mobile users in a network cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Such a hybrid construction can be classified into three categories: redundant systems, switch-over systems and load-balancing systems [40]. The redundant systems duplicate data and transmit them simultaneously over both the FSO and RF data links.…”
Section: Fso/rf Hybrid Data Linkmentioning
confidence: 99%
“…Such a hybrid construction can be classified into three categories: redundant systems, switch-over systems and load-balancing systems [40]. The redundant systems duplicate data and transmit them simultaneously over both the FSO and RF data links.…”
Section: Fso/rf Hybrid Data Linkmentioning
confidence: 99%
“…Free space optics transmission is subject to many research investigations because of its well-known advantages 8 . These optical systems are being preferred to microwave systems in cities and villages where the communication link distance is short.…”
Section: Related Work In Wireless Optical Transmissionmentioning
confidence: 99%
“…Satellite & Wireless Local Area Network (WLAN) combinationIn[34], combination of FSOC with satellite communication & WLAN in civil military cooperation (CIMIC) scenarios have been discussed. Various possible military applications based on integrating FSOC with wireless networking using Local Multipoint Distribution System (LMDS), satellite communications, Wireless LAN, and DVB-T (Terrestrial Digital Video Broadcast) have been demonstrated.…”
mentioning
confidence: 99%
“…The user's computer/laptop would be fitted with equipment compatible for DVB-T data (downlink) reception & a network interface card would connect to FSOC. It has also been brought out in[34] that an Earth station can be installed in military areas fitted with FSOC & WLAN can be effectively utilized for conducting a VC between various military bases or with military command areas and civil agencies like Fire Fighters, station police, Government departments etc. This much needed scenario of CIMIC has been undertaken in civil-military exercise in Austria.…”
mentioning
confidence: 99%
See 1 more Smart Citation